Sunflower Cost-Return Budget in North Central and Northeast Kansas - Dhuyvetter, Kevin C. (My University, 1998)
This publication provides estimated cost and returns for forward farm planning for producing sunflowers in north central and northeastern Kansas.
MF2144_1998_10
Keywords: MF2144; Crops; Economics; MF